Exploring the antecedents of organizational resilience practices – A transactive memory systems approach - Cotta, Diogo; Salvador, Fabrizio (Emerald Group Holdings Ltd., 2020)
Purpose: The purpose of this paper was to explore individual- and firm-level antecedents of the ability of a manufacturing firm's personnel to collaborate and integrate knowledge for organizational resilience practices. Design/methodology/approach: The authors apply hierarchical regression analysis to study a sample of 192 European industrial equipment manufacturers. Data for each firm are collected from surveys of two key informants in each firm,as well as from public sources. Findings: Firms' personnel’s ability to integrate information and knowledge for organizational resilience practices was positively related with the extent of the head of manufacturing's network of personal contacts inside the firm. This effect was stronger in firms with more formalized job descriptions and clearly defined roles. The head of manufacturing's orientation to teamwork and cooperation impacted this ability only in firms that did not financially incentivize cooperation. The authors also found that cooperation incentives and role formalization directly relate to firms' personnel’s ability to integrate information and knowledge for organizational resilience practices. Originality/value: The study proposes to study organizational resilience practices through a transactive memory systems lens. The study is also the first to link characteristics of individual managers to firm-level resilience practices by examining the antecedents of firms' ability to integrate information and knowledge to recover from operational disruptions. Furthermore,the study serves to enhance the knowledge of resilience practices by examining the role of firm-level antecedents and their interplay with characteristics of individual managers. © 2020,Diogo Cotta and Fabrizio Salvador.
Keywords: Manufacturing managers; Organizational resilience; Regression analysis; Transactive memory systems; 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 9 - Industria, innovación e infraestructura